CHAC1 Is Differentially Expressed in Normal and Cystic Fibrosis Bronchial Epithelial Cells and Regulates the Inflammatory Response Induced by Pseudomonas aeruginosa - Perra, Léa; Balloy, Viviane; Foussignière, Tobias; Moissenet, Didier; Petat, Hortense; Mungrue, Imran N.; Touqui, Lhousseine; Corvol, Harriet; Chignard, Michel; Guillot, Loic (Frontiers in Immunology, 2018)
In cystic fibrosis (CF), Pseudomonas aeruginosa (Pa) colonizes the lungs, leading to chronic inflammation of the bronchial epithelium. ChaC glutathione specific γ glutamylcyclotransferase 1 (CHAC1) mRNA is differentially expressed in primary human airway epithelial cells from bronchi (hAECBs) from patients with CF and healthy patients at baseline and upon infection with Pa. CHAC1 degrades glutathione and is associated with ER stress and apoptosis pathways. In this study, we examined the roles of CHAC1 in the inflammatory response and apoptosis in lung epithelial cells. First, we confirmed by reverse transcription quantitative polymerase chain reaction that CHAC1 mRNA was overexpressed in hAECBs from patients without CF compared with the expression in hAECBs from patients with CF upon Pa (PAK strain) infection. Moreover, the Pa virulence factors LPS and flagellin (F) were shown to induce CHAC1 expression in cells from patients without CF. Using NCI H292 lung epithelial cells, we found that LPS induced CHAC1 mRNA expression was PERK independent and involved ATF4. Additionally, using CHAC1 small interfering RNA, we showed that reduced CHAC1 expression in the context of LPS and F stimulation was associated with modulation of inflammatory markers and alteration of NF-κB signaling. Finally, we showed that Pa was not able to induce apoptosis in NCI H292 cells. Our results suggest that CHAC1 is involved in the regulation of inflammation in bronchial cells during Pa infection and may explain the excessive inflammation present in the respiratory tracts of patients with CF.